Analysis of Phytochemical Components in Fractionated Ethanol Extracts of Chrysophyllum albidum Leaves - Eneji Emmanuel A.; Yakubu O. E.; Imo Chinedu (Darul Yasin Al Sys, 2026)
Phytochemical characterization of medicinal plants is essential for guiding the isolation of bioactive constituents and supporting drug discovery efforts. This study comprehensively assessed the phytochemical composition of the ethanol leaf extract of Chrysophyllum albidum (C. albidum) using a complete gradient elution column chromatography methodology. The crude ethanol extract was fractionated into 12 fractions (F1–F12), with F1 being non-polar (100% hexane) and F12 being highly polar (100% water). All fractions were subjected to qualitative phytochemical screening to determine the presence of major phytochemical classes, including alkaloids, flavonoids, tannins, saponins, and terpenoids. The findings indicated a heterogeneous distribution of phytochemicals across the fractions, with elevated levels of polar constituents, particularly flavonoids and tannins, detected in the more polar fractions (F5–F11), whereas the less polar fractions (F1–F4) predominantly contained non-polar compounds such as terpenoids. This comprehensive phytochemical profile provides a valuable foundation for future bioactivity-guided isolation and characterization of specific bioactive compounds from C. albidum leaves, thereby supporting the development of phytopharmaceuticals derived from this species.